PEMBERDAYAAN EKONOMI MASYARAKAT MELALUI DANA DESA : SEBUAH KEBIJAKAN PEMERINTAH ACEH BARAT - Dinda Nurhanifa; Afrizal Tjoetra; Ikhsan Ikhsan (Universitas Teuku Umar, 2019)
This study aims to find out the implementation of West Aceh Regent Regulations Number 27 of 2017 concerning Guidelines for Community Economic Empowerment through Village Funds in Johan Pahlawan District. This study used a qualitative approach with descriptive methods and used the theories of Van Metter and Van Horn. The indicators consist of standards and policy objectives, policy resources, communication between related organizations and implementing activities, characteristics of implementing agents, social and political-economic conditions and attitudes of implementers or implementers. The results showed that the implementation of West Aceh Regent Regulation No. 27 of 2017 concerning Guidelines for Community Economic Empowerment through Village Funds in Johan Pahlawan Sub-District especially in Leuhan Village, Padang Seurahet Village, and Blang Beurandang Village had been carried out in accordance with the provisions of West Aceh Regent Regulation Number 27 the Year 2017. This is evidenced by the implementation of 2 (two) policy indicators, namely the distribution of empowerment assistance from village gampong to the community in accordance with policy standards and objectives, and human resources and the budget is adequate so that the response from the community is very enthusiastic about community economic empowerment activities through village funds. But in the implementation of West Aceh Regent Regulation Number 27 Year 2017 there are still 4 (four) obstacles based on the Van Meter and Van Horn theory, namely lack of socialization to the community so that the gampong community does not understand the standards, objectives and implementation mechanisms of West Aceh Regent Regulation Number 27 of 2017 and lack of communication and coordination between implementing agents of economic empowerment in 2017 with the current gampong government, then guidance and supervision not carried out thoroughly by policy implementers at the District and District levels, and implementers of empowerment activities at the village level did not fully carry out the verification process. towards empowerment proposals submitted by the community there are still some beneficiaries who are not eligible to be given economic empowerment assistance funds and are not strict enough to the recipients of economic empowerment benefits that cause low levels of compliance community beneficiaries of economic empowerment against sanctions and agreed conditions, then the external political environment that is not conducive is caused by-elections in 2017 where there is a change of regent, as well as lack of support and commitment from the implementing party at the village level to the implementation of regent regulations West Aceh Number 27 of 2017